1992
DOI: 10.1037/0022-3514.62.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Choice shift and group polarization: An analysis of the status of arguments and social decision schemes.

Abstract: Two Choice Dilemma Questionnaire items were used to investigate the influence of persuasive arguments and social decision schemes on group decisions. Furthermore, the predictions of the persuasive arguments theory on the polarization of individual preferences were tested. Ss were given lists of persuasive arguments and a 2nd individual decision was requested before the group discussion. The lists of persuasive arguments were compiled through a stepwise process of rating data gathered from the content analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 39 publications
0
50
0
3
Order By: Relevance
“…Luskin et al 2002;Farrar et al in press), but on the other hand, they may also lead to the amplification of certain errors, such as in fads and informational cascades, as briefly discussed at the end of this paper (e.g. Bikhchandani et al 1992;Zuber et al 1992;Sunstein 2002Sunstein , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Luskin et al 2002;Farrar et al in press), but on the other hand, they may also lead to the amplification of certain errors, such as in fads and informational cascades, as briefly discussed at the end of this paper (e.g. Bikhchandani et al 1992;Zuber et al 1992;Sunstein 2002Sunstein , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with El-Shinnawy & Vinzes', (1998) study that, individuals share relevant and factual information during group discussions and that, the other group members offer information or opinions helping an individual to view a situation from completely a new perspective from the one the individual previously held. Similarly, Meyers ' (1989) ;Zuber, et al, (1992) (2012) and Albarracina, et al, (2012) all confirm that information shared in a group and perceived as novel or new, original, valid or if the information is perceived to be true and credible, is more likely to influence the opinions of group members about the issues being discussed leading to group polarization.…”
Section: At First I Thought and Decided That We Could Look For Othermentioning
confidence: 96%
“…The findings indicated that, the discussion arguments were found to have increased the shifts in decisions after group discussions. Zuber, Crott & Werner, (1992) study reported that after arguments shared among group members the final group decisions showed a shift toward more extreme decision (3.39 vs. 3.59, P < 0.05), from the pre-group decisions, leading to group polarization. Tormala, Briñol & Petty, (2006) also found out that, the credibility of message determined how the message would be perceived by the people, for example, participants had greater confidence in their thoughts after learning that the source was high rather than low in credibility.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Johannes A. Zuber et al [2] define individual polarization as the change in individual preferences between two measures without group discussion or decision.…”
Section: Group Polarization and Public Perceptionmentioning
confidence: 99%